Recent Advances in the Catalytic Depolymerization of Lignin towards Phenolic Chemicals: A Review - Liu, Xudong; Bouxin, Florent P.; Fan, Jiajun; Budarin, Vitaliy L.; Hu, Changwei; Clark, James H. (ChemSusChem, 2020)
The efficient valorization of lignin could dictate the success of the 2nd generation biorefinery. Lignin, accounting for on average a third of the lignocellulosic biomass, is the most promising candidate for sustainable production of value‐added phenolics. However, the structural alteration induced during lignin isolation is often depleting its potential for value‐added chemicals. Recently, catalytic reductive depolymerization of lignin has appeared to be a promising and effective method for its valorization to obtain phenolic monomers. The present study systematically summarizes the far‐reaching and state‐of‐the‐art lignin valorization strategies during different stages, including conventional catalytic depolymerization of technical lignin, emerging reductive catalytic fractionation of protolignin, stabilization strategies to inhibit the undesired condensation reactions, and further catalytic upgrading of lignin‐derived monomers. Finally, the potential challenges for the future researches on the efficient valorization of lignin and possible solutions are proposed. “Lignin‐first” biorefinery: Catalytic valorization of lignin provides a promising and attractive strategy for producing value‐added phenolic monomers. The recent advances in catalytic depolymerization of technical lignin and reductive catalytic fractionation of protolignin are comprehensively summarized. The mechanism of condensation reactions and possible solutions are also discussed.